2008
DOI: 10.1088/0960-1317/18/5/055011
|View full text |Cite
|
Sign up to set email alerts
|

Fusion-bonded fluidic interconnects

Abstract: A new approach to realize fluidic interconnects based on the fusion bonding of glass tubes with silicon is presented. Fusion bond strength analyses have been carried out. Experiments with plain silicon wafers and coated with silicon oxide and silicon nitride are performed. The obtained results are discussed in terms of the homogeneity and strength of fusion bond. High pressure testing shows that the bond strength is large enough for most applications of fluidic interconnects. The bond strength for 525 µm thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In the work reported here, we have characterized the use of borosilicate glass tubes as fluidic interconnects. A preliminary study to this work was undertaken by Fazal et al and is reported elsewhere [7,8]. Our results demonstrate that the 3 mm inner diameter capillary connections can be safely operated at pressures of more than 7 MPa and that they are inherently hermetically sealed.…”
Section: Introductionsupporting
confidence: 50%
“…In the work reported here, we have characterized the use of borosilicate glass tubes as fluidic interconnects. A preliminary study to this work was undertaken by Fazal et al and is reported elsewhere [7,8]. Our results demonstrate that the 3 mm inner diameter capillary connections can be safely operated at pressures of more than 7 MPa and that they are inherently hermetically sealed.…”
Section: Introductionsupporting
confidence: 50%
“…Fazal et al performed a Pyrex-tube-to-silicon bond similar to that which we present at temperatures around 680 °C. To achieve proper bonding at this temperature, the rough surface of the diced tube was polished prior to bonding [11]. The objective of our approach was to avoid additional process steps such as polishing, which meant that a higher temperature (730 °C) was required for proper bonding.…”
Section: Discussion Of the Preliminary Testmentioning
confidence: 99%
“…This bond is described in several scientific reviews, including [8,10]. The new idea of a reflow bond process with Pyrex is described by Fazal et al in [11]. By heating up Pyrex above the glass transition temperature, it becomes viscoelastic and is able to flow.…”
Section: Components Of Borosilicate Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a syringe pump system with silicone rubber tubing is generally used as the external unit for operating fluids inside the microfluidic chip. Although there have been various efforts towards an integration method of the external unit into the microfluidic chip [13][14][15][16][17][18][19], complicated structures and/or sophisticated fabrication methods are mandatory in most cases. In this regard, the development of a simple interconnection scheme or novel fabrication method is considered as one of the most urgent for the practical application of various microfluidic chips.…”
Section: Introductionmentioning
confidence: 99%